Study of food security in rural Assam : Are food based welfare programmes doing enough? - Rahman, Mahsina (My University, 2017)
The poverty literature in India shows that the eastern region comprising Assam, Bihar, Odisha, and West Bengal have had the lowest growth rate in average per capita consumption expenditure and decline in poverty ratios since the 1990s. Direct and indirect estimates of poverty show rural Assam as being one of the poorest states of India (36.4 per cent and 87.5 per cent respectively in 2003-04). The official head count ratio of poverty for Assam stagnated in the period of 1990s and increased in the 2000s. The latest poverty estimates for the period of 2004-05 to 2009-10 shows poverty ratio in Assam to have increased by almost four percentage points (NSSO 61st and 66th rounds). The share of food expenditure in total household expenditure of rural Assam is very high (66 percent in 2004-05 and 64.4 per cent in 2009-10). Health outcome indicators such as maternal mortality (300 per one lakh live birth in 2013) and infant mortality are also one of the highest in Assam (54 per 1000 live birth in 2013). This thesis studies the three major components of National Food Security Act in India – targeted public distribution system (TPDS), Integrated Child Development Services (ICDS) and mid-day meal (MDM) programme. The major thrust of this thesis is to look at the contribution of food based welfare programmes to household level food security. Unlike many other Indian states, Government of Assam does not maintain a state buffer of foodgrains for public distribution system (PDS). Neither does it provide a state subsidy to the end consumers. Different state issue prices are specified for regions falling under plain, riverine and hill areas. Within these region categories, different state issue prices apply based upon the geographical distance from the Gram Panchayat Samabay Samiti (GPSS) to fair price shop (FPS). This difference in SIP is to cover the costs of transportation of the FPS dealers. Consequently, the prices charged from the end consumers also differ. Studies have shown that such different sets of prices charged from consumers led to information distortion and exclusion at the household level.
Bedamatta, Rajshree
Keywords: HUMANITIES AND SOCIAL SCIENCES